Kajian Kelayakan Finansial Perumahan Griya Mahoni Alue Penyareng - Edi Mawardi; Dian Febrianti; Zainal Abidin (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
West Aceh is one of the districts in the province of Aceh with an increasing number of residents also increasing the level of need for shelter. Demand for housing products can be known from the occupancy rate of other existing housing areas.Based on such circumstances, the writer wants to analyze the financial feasibility of property or investment in Griya Mahoni housing development activities.The purpose of this study is to determine the financial flow (cash flow) in the Griya Mahoni Alue Peunyareng housing development project and to estimate the level of financial feasibility if investing in the housing construction project.The research methods used in this study are the Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PBP) methods.Calculation of cash flow analysis with year period (n) or economic life of the project 15 years and the percentage of interest or rate of return is 5%, get PBP at an interest of 5% 0.631 years or 6 months.